Meaning in Life, Future Orientation and Support for Violent Radicalization Among Canadian College Students During the COVID-19 Pandemic - Miconi, Diana; Geenen, Gabrielle; Frounfelker, Rochelle L.; Levinsson, Anna; Rousseau, Cécile (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has increased levels of uncertainty and social polarization in our societies, compromising young people’s capacity to envision a positive future and maintain a meaningful sense of purpose in life. Within a positive youth development framework, the present study investigates the associations of a positive future orientation, presence of and search for meaning in life, and support for violent radicalization (VR) in a diverse sample of Canadian college students. In addition, we investigate the moderating role of future orientation in the association between presence of and search for a meaning in life and support for VR. A total of 3100 college students in Québec (Canada)(69% female; Mage = 18.57, SDage = 1.76) completed an online survey during the second wave of the COVID-19 pandemic. Results from linear mixed-effects models indicate that a positive future orientation and a higher presence of a meaning in life were negatively and independently associated with support for VR. Search for meaning in life was not associated with support for VR. The magnitude of the negative association between presence of a meaning in life and support for VR was greater among students with a more positive future orientation. Schools and colleges are in a privileged position to implement preventive interventions to support a positive future orientation and the presence of a meaning in life among young people during these challenging and uncertain times and reduce the risk of violence related to extreme ideologies in our rapidly changing society.